RANCARancang Bangun Website E-Learning Program Studi Pendidikan Jasmani, Kesehatan Dan Rekreasi Jurusan Ilmu Pendidikan FKIP Universitas Palangka Raya - Jadiaman Parhusip; Abertun Sagit Sahay; Antonius Nahak Marin (Universitas Palangka Raya, 2019)
Physical Education and Recreation Study Program is one of Study Programs of Education Stream of Faculty of Teacher and Education of Palangka Raya University. During this time, learning and teaching activity in Physical Education and Recreation Study Program (PJKR) happens with one condition in which there is a meeting between students and lecturer in a class. If the meeting does not happen this means the learning and teaching activity will be interrupted or delayed. To solve the problem of delayed learning and teaching activity, it is needed a certain facility which is available to maximize the learning and teaching process through the development of technology in education area. This is known as website e-learning. This website was constructed using PHP, database MySQL and also phases of waterfall software development method; Analysis and Definition of Need, System Plan and Software, Implementation and Test of Unit, Integration and Test of System, and Operation and Maintenance. The result of the blackbox test showed that website e-learning PJKR Program Study could manage feature of e-learning which were lecture materials and assignments or quizes. This e-learning ran well accordance with its design